Performance Analysis of the Medan City Social and Cemetery Service (Case Study: Guidance for Street Children) - Sri Sudiarti; Khayla Maya Amalia (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
Medan is the capital city of North Sumatra Province which is also concerned about the fate of street children. The number of street children in Medan City is significant enough to be considered as one of the social problems of the community. The local government of Medan made a concerted effort to eliminate street children in the city. The main purpose of the author's research is to find a means of providing training for street children. The authors of this paper investigate a qualitative analytical approach. While the descriptive analysis of the spoken words and observable behavior of the people being studied is the data analysis technique used. Based on the research findings, the data obtained from direct questions and answers to informants were analyzed, resulting in five elements of government functions as follows: (1) Service provision as a concept has been formulated adequately, but they lack the necessary facilities to support it, because only one has training facilities. (2) In terms of regulation, the City of Medan does not yet have a special regional regulation for street children; On the other hand, street children are only one of the studies contained in the Medan City Regulation Number 12 of 2008 concerning Social Order. (3) The coordination of the review is quite good, as can be seen from the joint raids by the Medan City Social and Cemetery Service, as well as other agencies that took to the streets together. (4) Representatives, members of the DPR who represent the people, who cooperate with the Medan City Social and Cemetery Service, and who receive special funds from the DPRD according to a special budget for the development of street children. (5) Development, the Social Service, and the Medan Cemetery, only have one forum, namely LBK, the latest condition is far from being maintained, and there has been no work on social problems at LBK until the end of this research. The burial of street children in Medan City in fostering development activities, among others, the construction of additional houses being built, and the need for understanding and support from all components of society and the government to resolve or at least reduce the problem of street children.